(untitled) (International Journal of Engineering and Computer Science, 2016)
The fields of computer science and electronics have merged to result into one of the most notable technological advances. Contemporary service innovation is to an important extent stimulated and enabled by developments of information technology[11]. A fairly recent technical development is labelled Internet of Things (IoT) based on the fact that also devices and objects are connected to the Internet. IoT also means that individual objects, and interrelated collections of objects e.g. in homes and cars, can be made uniquely identifiable by radio tags, sensors and actuators, and thereby become virtually represented in wireless and wired internet structures in the form of realization of the Internet of Things (IoT).The IoT has the potential to deliver solutions that dramatically improve energy efficiency, security, health, education and many other aspects of daily life. This paper discusses the vision, the challenges, possible usage scenarios[13][14] and technological building blocks of the “Internet of Things” and its various applications . This paper also discusses how the IoT is shaping the future of development and its challenges .